Household Food Insecurity and Its Association with Nutritional Status of Children 6–59 Months of Age in Kebridehar City - Aden, Ebrahim Hassen; Mohammed, Saleha Abdusamed (Indonesian Food and Nutrition Progress, 2024)
Malnutrition, characterized by an imbalance in the intake of calories, proteins, or other nutrients, includes undernutrition and overnutrition. This study aimed to assess the impact of household food insecurity on the nutritional status of children aged 6 to 59 months in Kebridehar town using a community-based cross-sectional approach. The city of Kebridehar was divided into 12 kebeles and the study targeted families with children in the specified age group. A proportional sample of 344 households was randomly selected from each kebele. Data were collected through surveys and analyzed to determine the prevalence of food insecurity and its effects on children's nutrition.Results: The study revealed significant disparities in food security: 11.6% of households were food secure, while 88.4% were food insecure. Female-headed homes had a lower percentage of impoverished children and the mother's education had a vital influence. Low- and middle-income households had a larger risk of childhood loss than higher-income ones. Smaller families were 15.76 times more likely to suffer food insecurity and homes without health services were 3.27 times higher potential to be food insecure. Children from insecure food families have poorer health outcomes, being 4.95 times more likely to be underweight, 1.30 times more likely to be stunted, and 1.45 times more likely to be wasted.Conclusion: The study highlights an important problem of food insecurity that affects the health of children. Factors such as the woman's family, the mother's education level, low income and family size are crucial. Urgent interventions are necessary to improve food security and nutritional outcomes, especially for families with low income, less education, and poor sanitation.